SOURCE STUDIES OF THE HISTORY OF AMIR TEMUR’S MILITARY CAMPAIGNS - Imamov Ulug’bek Ismailovich (Galaxy International Interdisciplinary Research Journal, 2023)
In the history of world civilization, there are many battles and how strong the composition of the army is, it is constantly studied chronologically. However, information about the purpose of these battles and the appearance of the troops, its true nature and subsequent consequences is rare. A similar phenomenon is observed in the topic of Amir Temur’s military campaigns. There is very little information about the combativeness of Amir Temur’s army and how it moved, as well as the directions of its invasion and the issues of its control. This article presents specific facts about the historiography of Amir Temur’s military campaigns and the composition of the army based on scarce information.